Effect of various technological parameters on particle morphology and uniformity of α-Ni(OH)2 synthesized via surfactant-free hydrothermal route. Issue 4 (1st March 2021) - Gul, Muhammad; Akhtar, Khalida
Abstract: Hierarchical microspheres of α -Ni(OH)2, uniform in size and shape, have been synthesized through a facile surfactant-free hydrothermal route. Experimental parameters such as reaction time, temperature and reactant concentration were systematically optimized to produce monodispersed particles. SEM analysis confirmed that the particles synthesized from a recipe containing 2.65 × 10 −2  mol. L −1 nickel chloride and 5.6 × 10 −1  mol. L −1 urea aged at 85 °C for 2 hours were uniform in size and morphology. HR-TEM results showed that the hierarchical microspheres are made up of thin sheet-like units. The crystal structure of the α-Ni(OH)2 microspheres was investigated by XRD which showed (003) as the preferred orientation plane having 7.369 Å interplanar spacing and crystallite size of 21 nm. The intercalation of CO3 −2 and OCN − species was revealed by FT-IR spectroscopy. The average activation energy (41.23 KJ mol −1 ) for thermal-induced transformation reaction was determined based on the TG/DTA data recorded at three heating rates. The present green and facile route could be extended to synthesize monodispersed systems of other metal compounds. Graphical Abstract: